2020
DOI: 10.36834/cmej.68486
|View full text |Cite
|
Sign up to set email alerts
|

National survey of Canadian residents and program directors regarding parental leave during residency

Abstract: Background: Despite the advantages of having a child as a medical resident, the transition back to residency after parental leave can be challenging. This study is the first to investigate this issue using a nation-wide Canadian sample of both residents and program directors. Method: A questionnaire was developed and made available online. Respondents included 437 female residents, 33 male residents, and 172 residency program directors. The mean length of parental leave was nine months for female residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“… 4 Indeed, there is some evidence that returning to work from parental leave results in self-reported sleep deprivation. 19 However, one study found that self-reported night awakenings and duration of wakefulness do not differ between working and non-working mothers of children 4–5 months old. 14 A problem with these studies is that self-reports of sleep are often poorly correlated with objective measures, such as actigraphy and polysomnography, eg, 20 and only a few studies have compared objectively measured sleep in couples with children.…”
Section: Introductionmentioning
confidence: 96%
“… 4 Indeed, there is some evidence that returning to work from parental leave results in self-reported sleep deprivation. 19 However, one study found that self-reported night awakenings and duration of wakefulness do not differ between working and non-working mothers of children 4–5 months old. 14 A problem with these studies is that self-reports of sleep are often poorly correlated with objective measures, such as actigraphy and polysomnography, eg, 20 and only a few studies have compared objectively measured sleep in couples with children.…”
Section: Introductionmentioning
confidence: 96%